Experiential Marketing and Customer Loyalty in Food and Beverage Industry - Sitti Hasbiah; Ilma Wulansari Hasdiansa (PT Maju Malaqbi Makkarana, 2023)
In the highly competitive café and restaurant industry, meeting customer desires is paramount to success. To achieve this, offering unique and value-added experiences alongside technological advancements is essential. This research adopts a quantitative approach, with experiential marketing variables as independent factors and customer loyalty as the dependent variable. Questionnaires were used for data collection, and the study has a cross-sectional time dimension. The sample comprises customers who visited Kampoeng Popsa Makassar at least twice. The study results demonstrate a significant influence of experiential marketing on customer loyalty, as indicated by the high mean values in each experiential marketing dimension. Notably, the